Cytoglobin expression in rat kidney during exposure to systemic chronic hypoxia - Ika Superti Daruningrum; Ani Retno Prijanti; Ninik Mudjihartini; Mohamad Sadikin; Sri Widia A Jusman (Acta Biochimica Indonesiana, 2020)
Background: The kidneys in physiological conditions are always in a state of relative hypoxia. Cytoglobin (Cygb) is the newest globin protein found of the globin family. One of the functions of Cygb is in oxygen supply. Cygb expression is found to increase in hypoxic conditions, which are thought to be an adaptation response to hypoxia. Objective: This study aimed to analyze the expression of Cygb in rat kidneys which were exposed to chronic systemic hypoxia. Methods: Twenty five male Sprague-Dawley rats, weighing 150-200 g were used in this experiment. Rats were divided into 5 groups: The control group was exposed to normoxia; the hypoxia groups (10% oxygen / 90% nitrogen) for 1 day; 3 days; 7 days and 14 days. After treatment, rats were sacrificed and their kidneys were taken. Cygb mRNA expression was measured by qRT-PCR, while Cygb protein expression was measured by the ELISA method. Results: The expressions of Cygb mRNA and protein were found to be highest on day 3 of hypoxia and was correlated very strongly and significantly (r2 = 0.96; p <0.05). Conclusion: The highest expression of Cygb on day 3 of chronic systemic hypoxia exposure is suggested as an attempt to restore oxygen supply to the kidneys.